A comparison of acoustic far-field prediction methods for turbulent flows. Issue 6 (October 2019) - Zhong, Siyang; Zhang, Xin; Huang, Xun
Spurious wave contaminations may occur in the computations of acoustic far-field directivities in turbulent flows with only surface integrations. Two methods could be used to tackle the problem: (1) to take average of the solutions using multiple integration surfaces based on the Ffowcs-Williams and Hawkings equation that was widely applied to various aeroacoustics problems, and (2) to use the generalized sound extrapolation method based on an indirect acoustic variable to filter out the non-acoustic fluctuations in turbulent flows. The performances of the two methods are investigated by applying to the representative broadband airfoil leading edge noise and turbulent jet noise problems. For the Ffowcs-Williams and Hawkings approach, the prediction accuracy is sensitively influenced by the number and location of the integration surfaces. It often requires more than 10 well-configured surfaces to yield a convergent solution compare to the indirect acoustic variable method. The properties of robust and low computation cost of the indirect acoustic variable method suggest that it is potentially useful for the far-field computations of the aeroacoustics problems.